Implementing Bandura's Social Learning Theory in Nursing Care: New Approach For Independence Nursing Practice - Mulyono, Wastu Adi (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Nurses exploits patients and their environment into nursing care plan to improve patients health status. One of goal of the nursing intervention is patients behavior into a more positive or constructive for their current condition due to their health condition. Bandura, through his Social Learning Theory, has offer solution. Nursing practice which expects patients change behaviour may consider this theory into nursing care. This article tries to describe how to implement the Social Learning Theory of Bandura into nursing care plan. Distress spiritual among cancer patients is depicted as background situation.